Development of a protocol for nursing care for relatives of patients hospitalized in na Intensive Care Unit (Research, Society and Development, 2023)
Objective: to describe the development of a protocol for the nursing care of family members of patients admitted to an Intensive Care Unit. Methodology: methodological study with technological production, based on the philosophy of Family-Centered Care and on the National Humanization Policy, developed in three stages: 1) literature review; 2) construction of a Protocol for the Care of Family Members of Patients in Intensive Care Units; and 3) validation of the technology content by 15 nurse judges, experts in the area, using the Content Validity Index - CVI. Results and discussion: after the validation process, the overall CVI of the protocol was 0.87, reaching the level of agreement equivalent to that determined by the index. The final version of the protocol includes in its composition: two care flowcharts, a form for admission of the family to the Intensive Care Unit, an orientation chart with the necessary interventions to meet the needs of family members of patients in the Intensive Care Unit. Final Considerations: The developed technology serves as a guide for the nurses' actions, facing the admission of the binomial patient-family and standardization of the good assistance practices already consolidated aiming at the care of the family in the ICU. Furthermore, it may influence changes in the planning and implementation of practices directed to the welcoming and humanization of the environment in view of the need to strengthen the presence of the family in the ICU. In addition, it may influence changes in the planning and implementation of practices aimed at welcoming and humanizing the environment in view of the need to strengthen the presence of the family in the family member's hospitalization process.